Energy competition and pairing effect for the fission path with a microscopic model - Fujio, Kazuki; Ebata, Shuichiro; Inakura, Tsunenori; Ishizuka, Chikako; Chiba, Satoshi (Frontiers in Physics, 2022)
We studied the fission barrier of ^236U with a microscopic mean-field model employing Skyrme-type effective interaction. It has been known that the microscopic mean-field calculation had a trend of overestimating the fission barriers derived from the fission cross section, and our results were found to be in accord with it. To reveal a major factor of the discrepancy, we investigated various components of the Skyrme energy-density functional building of the fission barrier height by a static mean-field model, including nuclear pairing correlation. We found that the spin-orbit and pairing terms affected the fine structure of the fission barrier as a function of elongation of the nucleus. Therefore, we investigated the sensitivity of the fission barrier height on the pairing strength, considering the change of level density along the calculated fission path.